Molecular Marker Analysis of Vitis vinifera `Albariño' and some Similar Grapevine Cultivars - Loureiro, M. Dolores; Martínez, M. Carmen; Boursiquot, Jean-Michel; This, Patrice (Journal of the American Society for Horticultural Science, 1998)
`Albariño' ( Vitis vinifera L.) is an important grape cultivar in Spain, morphologically diverse but subject to much misnaming. The objectives of the present work were to correct some of the more common misnamings concerning `Albariño' and to evaluate the genetic variability within this cultivar by analyzing DNA polymorphisms using randomly amplified polymorphic DNA (RAPD) markers and microsatellite techniques. Several accessions of `Albariño' (16 accessions from Misión Biológica de Galicia, one accession from El Encin, one accession from Rancho de la Merced), related cultivars (`Alvarinho', `Caíño blanco', `Cainho branco', `Loureiro'), and cultivars presumably identical to misnomers (`Savagnin blanc' and `Gewürztraminer') were analyzed using 20 RAPD markers and six microsatellite loci. Both techniques revealed polymorphism among `Albariño', `Caíño blanco', `Albariño' from Rancho de la Merced and `Loureiro'. No polymorphism was detected among the 16 `Albariño' accessions from Galicia, the `Albariño' accession from El Encin and `Alvarinho', nor among the `Albariño' accession from Rancho de la Merced, `Savagnin blanc' and `Gewürztraminer', nor between `Caíño blanco' and `Cainho branco'. These results enabled us to clarify the main misnomers concerning these cultivars. The absence of polymorphism among the true `Albariño' accessions did not allow the detection of any clonal variation. The suitability of both techniques for defining the cultivar level for grapevine is discussed.